RAIF – Reserved Alternative Investment Fund – The impact on the Luxembourg Fund Market and the Alternative Investment Fund landscape - Patrick Matthias Sprenker (European Institute for Knowledge & Value Management (EIKV), 2017)
Within the theme “RAIF – Reserved Alternative Investment Fund – The impact on the Luxembourg Fund Market and the Alternative Investment Fund landscape” this thesis will present the possible effects related to the introduction of the Reserved Alternative Investment Fund (RAIF) and its impact on the Luxembourg Alternative Investment Fund Industry. Especially Luxembourg's ability to diversify its product range and to extend its product offers by creating new and innovative fund structures attracts potential investors and initiators. These unique circumstances have an impact on the Alternative Investment Fund Industry. The aim of this thesis is to provide a detailed and comprehensive overview of the relevant fund business and its related regulations in order to access the RAIF within the current market environment and to investigate if such a product can positively influence the growth of the local Alternative Investment Fund Market. The current role of the Luxembourg Alternative Investment Fund Industry and its potential as well as the outcomes, derived from the analysis of the RAIF in relation to other available fund products, will be presented and evaluated based on a SWOT analysis. The gained theoretical insights will be compared with the practical and current market view of the product derived from five expert interviews, each conducted with a specialist in the specific field of the Alternative Investment Fund Industry in Luxembourg. In a final conclusion the findings and results, gained from the theoretical and practical part of this thesis, will be presented. The RAIF has a significant potential to become a well-established fund structure in the Luxembourg market. It reflects the level of creativity, flexibility and diversity of a market and its players within in a fast changing environment.
Keywords: 330